The Iranian Islamic Revolution : For better or for worse? - Zadeh, Jana; Lisa, Aleš, 1956-; Prorok, Vladimír, 1956-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The thesis focuses on the Islamic Revolution of Iran by a comparative analysis of the monarchy regimes before and after the Islamic Revolution of 1979. Although there is little doubt that the transformation of Imperial Iran to the Islamic Republic has played a vital catalyst in redrawing the "greater" Middle Eastern geopolitics ever since this thesis aims to compare the historical development of Iran during the monarchy and the effect of the revolutionary institutions brought on the Iranian society. Despite the extensive amount of resources used in this thesis being both from Iran and abroad, the author has made every effort to reduce the effects of the influences whether from the overzealous defenders of monarchy or the die-hard revolutionaries to a bare minimum and allow the facts on their own to project the picture through an objective lens. The goal of the thesis is for the objective research and comparison to try and provide a factual answer to the million-dollar question, whether the revolution was for better or for worse.
Vedoucí práce: Aleš Lisa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: politologie [obor dipl. práce]; diplomové práce; master's theses